Clinical and Pathological Correlation in Pediatric Invasive Pulmonary Aspergillosis - Anantasit, Nattachai; Nuntacharruksa, Noramon; Incharoen, Pimpin; Preutthipan, Aroonwan (Frontiers in Pediatrics, 2018)
Introduction: Invasive pulmonary aspergillosis (IPA) has been one of the major causes of mortality in immunocompromised patients. The gold standard method for a diagnosis of IPA is histopathological examination of the lung tissue; however, post-procedural bleeding limits the feasibility of lung biopsy. The European Organization for Research and Treatment of Cancer/Invasive Fungal Infections Cooperative Group and The National Institute of Allergy and Infectious Disease Mycoses Study Group (EORTC/MSG) defined IPA. The objective of this study was to validate the EORTC/MSG 2008 definition of IPA, compared with histopathology in the pediatric population. Methods: Histopathological examinations of lung tissues of children aged 1 month to 18 years with respiratory tract infection at the time of obtaining biopsy were retrieved. Retrospective chart reviews for clinical characteristics were performed. IPA diagnosis was classified according to the EORTC/MSG 2008 definition. Results: During the 10-year period, there were 256 lung tissues, of which 58 specimens were suspected to have pulmonary infection. Fourteen patients (24%) were noted to have IPA. Seven patients (50%) with proven IPA were classified as probable, whilst the remaining 50% were classified as possible, and none were classified as no IPA, by using EORTC/MSG 2008 definition. Other 44 specimens demonstrated 14 (32%), 14 (32%) and 16 (36%) were classified as probable, possible, and no IPA, respectively. When comparing probable or possible IPA with no IPA, we found that the EORTC/MSG 2008 definition had 100% sensitivity, 36% specificity, 33% positive predictive value, and 100% negative predictive value in diagnosis of IPA. Conclusion: Our study illustrated that the EORTC/MSG 2008 definition provided an excellent sensitivity but low specificity for diagnosing IPA. Keywords: Invasive pulmonary aspergillosis, pediatric, histopathology, definition, sensitivity. Word count: Abstract 266 words, text 1,949 words, 3 tables, and 1 figure